ISLAMIST POLITICS AND THE LOCAL GOVERNMENT ELECTION IN BANGLADESHI NEWSPAPERS: Received: 23rd January 2024 Revised: 7th February 2024, 8th April 2024, 12th April 2024 Accepted: 28th January 2024 - Md. Rana Mia, (PEOPLE: International Journal of Social Sciences, 2024)
This study aims to examine the representation of an Islamist political party— Islami Andolan Bangladesh (IAB) during their political campaign in the context of the 2023 Barishal City Corporation (BCC) in three Bangladeshi mainstream newspapers— the Daily Star (DS), the Daily Janakantha (DJ) and the New Age (NA). Examining the news articles, photographs and editorials, this study argues that these newspapers sidelined, ignored, and in some cases favored the Islamist party. It also argues that the party IAB uses myth— if you vote for hand-fan (electoral symbol of IAB), Allah and Rasool (prophet Muhammad) will have the votes; and makes voters sewer placing hands on the holy Quran—were unchallenged by the three newspapers. Though the IAB could not win the election, it was expected that mass media as social institutions would come forward with accurate information so that social members would not be misguided. The DS and DJ are found with the propensity to sideline and ignore the IAB and its electioneering. On the contrary, the NA provided balanced news coverage compared to the other dailies. Nonetheless, none of them have challenged the myth that the IAB’s uses of myth that misguided the voters.